Optimisation of an extraction technique of fish allergens suitable for detection and diagnosis - Jiaju Ma; Tushar Ramesh Pavase; Zhen-Xing Li; Hong Lin (Czech Journal of Food Sciences, 2017)
An optimised protocol for the extraction of allergenic proteins in fish was developed. Twelve existing or modified extraction buffers were evaluated based on the amount and quality of obtained 12 kDa IgG-binding protein (major fish allergen parvalbumin) by SDS-PAGE, immunoblotting, and ELISA. The results indicated that using DL-Dithiothreitol during the extraction process, the stability and functionality of the final extract were significantly increased. Solution 3 (containing Tris-HCl, Glycine, and DL-Dithiothreitol) yielded the highest amount of parvalbumin. The extract also induced a higher allergenic reactivity to the three tested human sera by immunoblotting. The results indicated that solution 3 provided better results in fish allergen detection and diagnosis. In conclusion, our study discovered and established solution 3 (Tris-HCl + Glycine + DTT) as the most potential buffer to overcome the conventional allergen extraction buffer and therefore it is highly recommended as a substitute optimised extraction buffer.